Phagocytosis of Apoptotic Cells Is Specifically Upregulated in ApoE4 Expressing Microglia in vitro - Muth, Christiane; Hartmann, Alexander; Sepulveda-Falla, Diego; Glatzel, Markus; Krasemann, Susanne (Frontiers in Cellular Neuroscience, 2019)
Alzheimer's disease (AD) is characterized by intracellular tau aggregates and extracellular deposition of amyloid-ß (Aß). The major genetic risk factor to develop AD is the Apolipoprotein E isoform 4 (ApoE4). ApoE4 may directly affect Aß pathology, yet the exact role of ApoE4 in the progression of AD remains unclear. Although astrocytes are the main source of ApoE in brain tissue, other cell types might contribute to ApoE isotype-dependent effects. While ApoE expression does not play a relevant role in homeostatic microglia, we and others could recently show that ApoE expression is significant upregulated in disease-associated microglia including AD-mouse models and human AD. ApoE has been supposed to have an anti-inflammatory effect, with ApoE4 being less effective than ApoE3. However, ApoE-isotype specific effects on microglia function in disease have not been thoroughly investigated to date. In contrast to this, the role of ApoE2, the third most common major ApoE isoform, in neurodegeneration has not been characterized in detail, but it has been shown to delay the onset of disease in familial AD. To elucidate the differential roles of the three-major human ApoE isoforms on microglia function we each expressed the human ApoE isoforms in murine N9 microglia cells. We could show that ApoE4 specifically influences actin cytoskeleton rearrangement and morphology. In migration assays, ApoE4 significantly promotes cell motility. To quantify phagocytosis by microglia we established an uptake assay based on imaging flow cytometry. Although expression of ApoE4 led to significantly reduced uptake of Aß in contrast to the other isoforms, we could show that ApoE4 specifically increased phagocytosis of apoptotic neuronal cells. Our findings show that ApoE4 intrinsically affects microglia physiology by upregulating motility and phagocytic behavior in vitro and may therefore specifically contribute to microglia dysregulation in AD.